Information technology essentials for behavioral health clinicians - Dewan, Naakesh A. (Health informatics., 2011)
Technology will drive behavioral health innovations in efficiency and quality, this book is great primer for clinicians, students, and decision makers on how to approach technology in behavioral health? David K. Nace M.D. Vice President, Clinical Development, McKesson Health Solutions, Philadelphia, PA, USA||Information Technology is only beginning to innovate and transform the practice and performance of clinicians in behavioral healthcare. Minimal investments in information technology research and development are fundamentally altering the lives of millions worldwide. This promise and future of behavioral informatics is outlined in the chapters that follow.||Information Technology Essentials for Behavioral Health Clinicians offers an overview the entire landscape of behavioral informatics, including practical technologies and discussions regarding privacy and security. Detailed discussions also focus on the clinician, their knowledge, care, and technology developments and tools. The book then goes on to review the technologies driven by the recipient of care and concludes with a section focusing on the organization and leaderships issues involved in transforming a behavioral health care organization into modern technology supported systems of care.||The world renowned editors have crafted a book in collaboration with nationally recognized experts in the field ? physicians, psychologists, informatics executives, researchers, social workers, engineers, and sociologists ? the diversity of perspectives bringing richness to the book and making it essential reading for students and faculty in departments of psychiatry, psychology, social work, other human service disciplines, and informatics departments.